(untitled) (Conference on English Language Teaching, 2023)
Code-switching in naturalistic discourse occurs when a speaker and an interlocutor share more than one language. It becomes the alternation in the classroom interaction to fill linguistics gap between teacher and students in learning process. The main aim of the research is to reveal code-switching phenomenon that happens in the classroom English speaking interaction. It classifies by several classification such types, functions, and reason of code-switching as part of Sociolinguistics phenomenon. Total respondent of this research followed by 40 students and 1 lecturer at Muhammadiyah University. The study was used descriptive qualitative to obtain a ’straight description of the phenomena’ and to provide analysis and interpretation of the research data. The data in form of utterances contained code-switching are written in the data sheet. The class observation was conducted for three weeks in each setting. To back-up the data gathering, a tape-recording technique was applied in the observation. The obtained data are selected, coded, and analyzed from sociolinguistics aspects. During open coding, the researcher identifies words, phrases, or events that appear were grouped into several categories. The result reveals code-switching phenomenon that mostly arise are Intra-sentential type, Phatic Function, and To Amplify and Emphasize a Point as reason aspect.